Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/met9060681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3 on the Formation of Calcium Ferrite in the Solid State

Abstract: Pure chemical reagents Fe2O3, Al2O3, and Ca(OH)2 were used to investigate the formation of calcium ferrite in the solid state. The phase composition of the prepared samples was determined using X-ray powder diffraction and by SEM. The TG-DSC analysis was performed to analyze the decomposition behavior and formation of calcium ferrites. The formation rate of calcium ferrite was determined by in-situ X-ray diffraction (XRD) and by the K-value method. The X-ray diffraction analysis was performed using Pt as the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was reported that when more than approximately 4.76 mass% Al 2 O 3 is added, all the CF is exhausted, and the CFA phase is present. In addition, according to Bai et al [22], as the Al 2 O 3 content increases from 1.4% to 2.8%, the total amount of CF decreases slightly. When the Al 2 O 3 content is greater than 2.8%, the CF content significantly decreases with increasing Al 2 O 3 content.…”
Section: Influence Of Al2o3 On the Metastable Samplementioning
confidence: 91%
“…It was reported that when more than approximately 4.76 mass% Al 2 O 3 is added, all the CF is exhausted, and the CFA phase is present. In addition, according to Bai et al [22], as the Al 2 O 3 content increases from 1.4% to 2.8%, the total amount of CF decreases slightly. When the Al 2 O 3 content is greater than 2.8%, the CF content significantly decreases with increasing Al 2 O 3 content.…”
Section: Influence Of Al2o3 On the Metastable Samplementioning
confidence: 91%